Hydrophobically modified polysaccharide-based on polysialic acid nanoparticles as carriers for anticancer drugs - Jung, Bom; Shim, Man-Kyu; Park, Min-Ju; Jang, Eun Hyang; Yoon, Hong Yeol; Kim, Kwangmeyung; Kim, Jong-Ho (ELSEVIER SCIENCE BV, 2017)
This study presented the development of hydrophobically modified polysialic acid (HPSA) nanoparticles, a novel anticancer drug nanocarrier that increases therapeutic efficacy without causing nonspecific toxicity towards normal cells. HPSA nanoparticles were prepared by 1-ethy1-3-(3-dimethylaminopropy1)-carbodiimide (EDC)/N-hydroxysuccinimide (NHS) coupling between N-deacetylated polysialic acid (PSA) and 5 beta-cholanic acid. The physicochemical characteristics of HPSA nanoparticles (zeta potential, morphology and size) were measured, and in vitro cytotoxicity and cellular uptake of PSA and HPSA nanoparticles were tested in A549 cells. In vivo cancer targeting of HPSA nanoparticles was evaluated by labeling PSA and HPSA nanoparticles with Cy5.5, a near-infrared fluorescent dye, for imaging. HPSA nanoparticles showed improved cancer-targeting ability compared with PSA. Doxorubicin-loaded HPSA (DOX-HPSA) nanoparticles were prepared using a simple dialysis method. An analysis of the in vitro drug-release profile and drug-delivery behavior showed that DOX was effectively released from DOX-HPSA nanoparticles. In vivo cancer therapy with DOX-HPSA nanoparticles in mice showed antitumor effects that resembled those of free DOX. Moreover, DOX-HPSA nanoparticles had low toxicity toward other organs, reflecting their tumor-targeting property. Hence, HPSA nanoparticles are considered a potential nanocarrier for anticancer agents. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ENHANCED PERMEABILITY; CANCER-CHEMOTHERAPY; POLYMERIC DRUGS; PHARMACOKINETICS; ASPARAGINASE; DELIVERY